2010
DOI: 10.1007/s00264-010-0976-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year migration results of the ReCap hip resurfacing system—a radiostereometric follow-up study of 23 hips

Abstract: There has been renewed interest for metal-on-metal hip resurfacing due to improved design and manufacturing of implants, better materials, and enhanced implant fixation. In contrast to conventional total hip replacements, only a few clinical hip resurfacing trials using radiostereometry (RSA) have been reported, and solely for the Birmingham hip resurfacing arthroplasty. The purpose of this RSA trial was to describe the migration pattern of a new hip resurfacing system (ReCap) within the first two years after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…1,10,11,1820 Gross et al 21 attributed <1% of their revisions to ARMD which is similar to our series. Baad-Hansen et al 20 found no rotation or migration of the components in their series based on radioisometric analysis at 2 years. Van der Weegan et al 1 had good to excellent results in 94% of cases in their follow-up of 3 years.…”
Section: Discussionsupporting
confidence: 90%
“…1,10,11,1820 Gross et al 21 attributed <1% of their revisions to ARMD which is similar to our series. Baad-Hansen et al 20 found no rotation or migration of the components in their series based on radioisometric analysis at 2 years. Van der Weegan et al 1 had good to excellent results in 94% of cases in their follow-up of 3 years.…”
Section: Discussionsupporting
confidence: 90%
“…Baad-Hansen et al conducted a radiostereometric analysis (n = 23). There was no statistically significant translation or rotation of the femoral component observed after two years FU [8]. The absence of any revisions in these series might be due to the small number of patients and the short FU.…”
Section: Discussionmentioning
confidence: 97%
“…Gagala reported there were no significant complications after a maximum follow up (FU) of 20 months, using this implant design (n = 23) [7]. Baad-Hansen reported no significant translation or rotation using this implant design (n = 25), after two year FU using radiostereometry (RSA) [8]. A larger number of ReCap procedures (n = 137) with a three year FU are described in the Australian National Joint Replacement Registry.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no other studies which have investigated the prevalence of pseudotumours with this particular HRA design using imaging modalities other than plain radiographs. The studies by Baad-Hansen and Gagala were limited to 23 and 25 HRA patients respectively with a maximum follow-up of 24 months (23, 24), Gross and Liu recently published a case series of 740 consecutive procedures with the ReCap HRA design with a follow-up of seven years maximum (25). The reported Kaplan-Meier survivorship with any revision as an end point was 96.4% at 7 years, with only two revisions (0.3%) for adverse wear.…”
Section: Discussionmentioning
confidence: 99%